(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article is based on the analysis of the failure to apply the pro persona principle in family proceedings in Tabasco, in particular in Trials where minors intervene, whether it is Guardianship and Custody, Family Controversy, Alimony, Divorces, Affiliations, Paternity in recognition as in ignorance, among others, this being a Human Right (DH) enshrined in Article 1 of the Political Constitution of the United Mexican States (CPEUM) and in various International Treaties, Sentences issued by international organizations, as well as multiple jurisprudential criteria pronounced by our Supreme Court of Justice of the Nation (SCJN). In the State of Tabasco, in view of the problems that arise in the family nucleus, due to the constant demands that are registered daily in the various Family and Civil Courts, as is the case of the aforementioned Family Trials, it is necessary that the Family and Civil Judges are bound to apply the pro person principle and the pro-child principle or the best interests of girls, boys and adolescents. These principles consist in applying, in the broadest sense, what is most beneficial to a minor, in any trial in which he is involved, so that the judge in the specific case of custody when filing or initiating the demand, must officially decree provisional coexistence, listen to minors urgently, even if the parties do not request it; scenario that currently the Judges, both Family and Civil in our entity, do not respect or apply, being a human right enshrined in articles 1, second paragraph and 4, ninth and tenth paragraphs of our Constitution.